SPECIFIC FEATURES OF THE ICE SHEET DYNAMICS IN EASTERN ANTARCTICA - Markov A.N.; Kotlyakov V.M. (My University, 2006)
Current ideas on the dynamics of the Antarctic ice sheet are based on geodetic observations that only register the glacier surface flow, whereas theoretical models of dynamic processes inside the ice sheet are of a hypothetical nature due to the lack of actual measurements of parameters of ice flow inside the glacier mass. The task of this study was to determine the real pattern of the ice mass dynamics inside the ice sheet on the vast territory of eastern Antarctica based on actual measurements in boreholes.